A novel anammox process combined with vibration technology. (May 2018) - Zhang, Kuo; Yang, Bo; Ma, Yongguang; Lyu, Liting; Pan, Yuan; Wang, Youzhao; Li, He; Zhu, Tong
Graphical abstract: Highlights: The growth and activity of the anammox bacteria were greatly enhanced with vibration. The highest nitrogen removal rate obtained under resonance state. The relative abundance of Planctomycetes increased to 71.4% in vibration reactor. Abstract: This study investigated a fixed bed anammox bioreactor that uses vibration techniques to treat synthetic inorganic wastewater. Continuous experiments indicated that the activity elevation period could be shorten to one third, when the nitrogen removal rate (NRR) reached 1 kg·N/m 3 ·d with vibration. R2 achieved the maximum NRR of 3.3 kg·N/m 3 ·d under the resonance state, which was 1.8 times higher than the control reactor. Analysis of vibration intensity suggested that anammox activity would be great improved with the increasing vibration. These results indicated that vibration played a key role in system performance. Furthermore, high-throughput sequencing showed that the reactor with the vibration had a higher proportion of anammox bacteria, which increased 7 times than the biofilm formation phase. Meanwhile, the proportion of Proteobacteria and Chloroflexi decreased by 37.1% and 7.78%, respectively. These results suggest that vibration could increase the anammox treatment performance and provide a better condition for the anammox bacteria.